Application of the Box-Behnken Experimental Design to Optimize Coffee Ground Oil Extraction Using the Soxhlet Method - Misbahudin Alhanif; Desi Riana Saputri; Khofifah Anggitiya Ningrum; Angeline Nauli; Fauzi Yusupandi; Yusuf Ma’rifat Fajar Azis; Maulidah Az Zahra; Hanif Fawaz Zaim (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2026)
Coffee is a widely traded and consumed commodity worldwide. In 2023, Indonesia's coffee consumption reached 312,000 tons, placing it as the second-largest consumer in Asia. This high consumption generates approximately 48% of coffee grounds as waste, which still contains valuable compounds such as carbohydrates, proteins, oils, minerals, and polyphenols, thus potentially being utilized in various applications. This study was conducted to optimize the Soxhlet extraction of oil from spent coffee grounds (SCGs), with the objective of maximizing yield while preserving oil quality. The investigated independent variables comprised the ethanol concentration in n-hexane (0, 50, and 100% v/v), extraction time (15, 30, and 45 min), and the solvent-to-solid (L/S) ratios (15:1, 20:1, and 25:1 mL/g), all systematically arranged using a Box–Behnken design (BBD). The study found that using ethanol – n-hexane mixtures at certain compositions significantly improved oil yield while reducing saponification value, acid value, and FFA content. Longer extraction times and higher L/S ratios also contributed to increasing yield and saponification value, while decreasing acid value and FFA up to an optimum point. The optimum condition was obtained at 17.89% v/v ethanol in n-hexane, 45 minutes of extraction, and a L/S ratio of 22.47 mL/g, resulting in a 25.34% yield with oil characteristics of 179.12 mg KOH/g saponification value, 4.30 mg KOH/g acid value, and 0.73% FFA. These findings demonstrate that Soxhlet extraction can produce SCG oil with favorable characteristics, although the saponification value was slightly lower (-0.49%) than the minimum limit set by SNI 7431:2015. Overall, SCG oil shows great potential as an alternative vegetable oil for use in food, pharmaceutical, cosmetic, and renewable energy applications.